Analisa Keuangan Sebelum, Selama, dan Sesudah Pandemi Covid-19 Pada PT Lippo Karawaci Tbk - Sarah, Sitti; Rachmawaty, Rachmawaty (Madani: Jurnal Ilmiah Multidisiplin, 2025)
This research aims to analyze the financial performance of PT Lippo Karawaci Tbk in the period of the first quarter of 2018 (Q1 2018) to the fourth quarter of 2023 (Q4 2023) using financial ratios including Current Ratio (CR), Quick Debt to Ratio (QER), Quick Debt Ratio (QR), Ratio (DAR), Return on Assets (ROA), Return on Equity (ROE), and Total Asset Turnover (TATO). Analyzes were conducted by comparing ratio values against industry standards and dividing them into three phases: before, during, and after the COVID-19 pandemic. The results of the study show that the liquidity and solvency levels of the company are best classified, indicated by the CR and QR values being well above the standard as well as the DER and DAR within reasonable limits. In contrast, the profitability to activity ratios were below industry standards, with significant declines in the pandemic period. Entering 2023, performance started to improve marked by positive ROA and ROE as well as improved TATO.